"Don't they jump on the seats?" The underrepresentation of migrant and minority artists in the cultural labour market of Brussels. Issue 15 (18th November 2022) - Swyngedouw, Eva
ABSTRACT: While migration has made cities more super-diverse than ever, artists with migrant backgrounds are underrepresented in the creative and cultural industries. Although existing literature pays attention to minorities' unequal labour market access, the question of how the careers and working conditions of artists with a migrant background play out in local cultural labour markets remains underexplored. Based on the case of the performing arts sector in Brussels, I outline the factors that explain the gap in cultural labour market representation between ethnic minorities and the white majority population. I contend that minority artists have more difficulties in entering the cultural labour market than native artists because they face structural and personal hurdles throughout their careers. Furthermore, I show that minority artists develop various strategies to overcome these barriers. This paper uncovers the mechanisms that contribute to the emergence and persistence of this "creative mismatch" in local cultural labour markets.